2015
DOI: 10.1007/s11920-015-0625-6
|View full text |Cite
|
Sign up to set email alerts
|

The Preeminence of Early Life Trauma as a Risk Factor for Worsened Long-Term Health Outcomes in Women

Abstract: Early life trauma (ELT) comprises an array of disturbingly common distressing experiences between conception and the beginning of adulthood with numerous and significant potential long-term, even transgenerational, health consequences of great public health concern, including depression, cardiovascular disease, and other psychiatric and medical disorders, and neurobiological, psychological, and behavioral effects which are sufficiently robust to confound many types of biomedical research. The impact of ELT on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 132 publications
2
15
0
Order By: Relevance
“…Consistent with prior findings (4,5,14), adding ELS to the model significantly increased overall performance (Δχ 2 = 5.88, Δdf = 1, P = 0.025) (Table S3). Within this model, the likelihood of achieving functional remission was negatively associated with ELS status [unstandardized beta coefficient (B) = −0.99, Wald statistic (W) = −2.12, P = 0.034] when holding covariates at a fixed value.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Consistent with prior findings (4,5,14), adding ELS to the model significantly increased overall performance (Δχ 2 = 5.88, Δdf = 1, P = 0.025) (Table S3). Within this model, the likelihood of achieving functional remission was negatively associated with ELS status [unstandardized beta coefficient (B) = −0.99, Wald statistic (W) = −2.12, P = 0.034] when holding covariates at a fixed value.…”
Section: Resultssupporting
confidence: 87%
“…ELS has been shown to moderate antidepressant outcomes (4,5,14,30). Consistent with these reports, we found that the severity of exposure to ELS in childhood is associated with a greater likelihood of treatment failure across three commonly prescribed antidepressants.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…amygdala | early life stress | human brain imaging | predictive biomarkers | antidepressant remission A mygdala reactivity and exposure to early life stress (ELS) are both strongly implicated in depression mechanisms in both animal and human models (1)(2)(3)(4)(5)(6). The amygdala plays an important role in emotion processing, including evaluating biologically salient emotional stimuli, generating emotional states and potentiating emotional memories (7).…”
mentioning
confidence: 99%